A Blockchain Prediction Model on Time, Value, and Purchase Based on Markov Chain and Queuing Theory in Stock Trade. (9th November 2020) - Lian, Wenjuan; Fan, Qi; Jia, Bin; Liang, Yongquan
Abstract : With the continuous development of the blockchain, it has brought a subversive impact on the blossom of all fields with its characteristics of decentralization, trust-free, and tampering, especially in the financial field. It is of great significance to research the application of blockchain technology in the financial field. As an important part of the financial market, stock has the crucial influence, and the combination of stock and blockchain is becoming a growing trend. In recent years, many studies have focused on the prediction of the stock value, but they have not fully considered the combination of time, value, and purchase. To solve the above problem, we propose a preemption queuing model for multipriority service objects in the blockchain financial architecture according to different service priority. Meanwhile, a queuing-based resource scheduling model is established by using the Markov chain to find the optimal solution. The method in this paper can greatly improve the efficiency of the system and provide a basis for future scientific research in the healthy and sustainable development of the securities industry.